Human CD34+-derived plasmacytoid dendritic cells as surrogates for primary pDCs and potential cancer immunotherapy - Fiore, Giovanna; Weckwarth, Wolfgang; Paetzold, Kerstin; Albertí Servera, Llucia; Gies, Manuela; Rosenhauer, Jakob; Antoniolli, Martina; Nassiri, Sina; Schmeing, Stephan; Dettling, Steffen; Soni, Bhavesh; Majety, Meher; et al. (Frontiers in Immunology, 2024)
Plasmacytoid dendritic cells (pDCs) are capable of triggering broad immune responses, yet, their scarcity in blood coupled to their reduced functionality in cancer, makes their therapeutic use for in situ activation or vaccination challenging. We designed an in vitro differentiation protocol tailored for human pDCs from cord-blood (CB) hematopoietic stem cells and report the generation of 200 pDCs per hematopoietic stem cell. We highlight the role of StemRegenin 1 and GM-CSF supplementation in enhancing IFN-α responses. In-depth characterization of CB-pDCs revealed a robust resemblance to primary pDCs phenotypically and functionally. Transcriptomic analysis confirmed strong homology both at baseline and upon TLR9 or TLR7 stimulation. Further, we could confirm the potential of CB-pDCs to elicit cytokines associated with NK and T cell recruitment and cytolytic functions upon TLR7-stimulation ex vivo in patient tumor explants. This study highlights CB-pDCs as surrogates for primary pDCs and their potential for cell therapy in cancer.